Optimasi vitamin C terhadap pertumbuhan dan kelangsungan hidup ikan nila (Oreochromis niloticus) yang diinfeksi Aeromonas hydrophila - Tondi, Devano Baga; Wijayanti, Ni Putu Putri; Pebriani, Dewa Ayu Angga (Jurnal Biologi Udayana; Vol 27 No 2 (2023): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2023.v27.i02.p05, 2023)
This study's goal is to ascertain the effects of supplying vitamin C to the growth and SR of Tilapia fish that have been infected with Aeromonas hydrophila . The study utilized an experimental approach, involving four different treatments and three replications. Tilapia fish measuring ± 25 cm and weighing 200-250 g. Treatment A (control), treatment B adds 500 mg/kg of vitamin C to the feed, treatment C adds 1000 mg/kg, and treatment D adds 1500 mg/kg of vitamin C to the feed. Each treatment received an infection of Aeromonas hydrophila at a density of 10 6 CFU/mL. The Aeromonas hydrophila bacterial culture's results were dissolved in the water to cause infection. Giving different doses of vitamin C to tilapia infected by Aeromonas hydrophila showed a noticeable variation (P<0.05) in the growth, but there was no significant difference (P>0.05) observed in the SR. Treatment B saw the largest growth in weight and length at 66.7 g and 3.09 cm. Treatment B has the highest SR, with 86.7%. The water quality range is classified as suitable for tilapia growth and SR. With a range value temparature of 27.58-27.72 °C, DO 4.10-4.65 mg/L, and pH 7.48-7.56. Vitamin C can improve tilapia SR and growth as well as affect the values of length and weight growth.